Neutralizing Interleukin-1β (IL-1β) Induces β-Cell Survival by Maintaining PDX1 Protein Nuclear Localization - Ardestani, Amin (American Society for Biochemistry and Molecular Biology, 2011)
The transcription factor PDX1 plays a critical role during β-cell development and in glucose-induced insulin gene transcription in adult β-cells. Acute glucose exposure leads to translocalization of PDX1 to the nucleoplasm, whereas under conditions of oxidative stress, PDX1 shuttles from the nucleus to the cytosol. Here we show that cytosolic PDX1 expression correlated with β-cell failure in diabetes. In isolated islets from patients with type 2 diabetes and from diabetic mice, we found opposite regulation of insulin and PDX1 mRNA; insulin was decreased in diabetes, but PDX1 was increased. This suggests that elevated PDX1 mRNA levels may be insufficient to regulate insulin. In diabetic islets, PDX1 protein was localized in the cytosol, whereas in non-diabetic controls, PDX1 was in the nucleus. In contrast, overexpression of either IL-1 receptor antagonist or shuttling-deficient PDX1 restored β-cell survival and function and PDX1 nuclear localization. Our results show that nuclear localization of PDX1 is essential for a functional β-cell and provides a novel mechanism of the protective effect of IL-1 receptor antagonist on β-cell survival and function.